Harald Szeemann : with by through because towards despite ; catalogue of all exhibitions 1957-2005 - Szeemann, Harald; Bezzola, Tobia; Kurzmeyer, Roman (Zürich : Edition Voldemeer ; Wien ; New York : Springer, 2007)
"This catalogue of all Harald Szeemann's exhibitions is a compendium of materials and sources relating to the work of the most celebrated independent organiser of exhibitions in the latter part of the 20th century"--Page 7.
Text primarily in English, with sections in several other languages.
Supplement: From the publisher to our Chinese readers (in Chinese).
boek
Keywords: Szeemann, Harald -- Catalogs; Szeemann, Harald; Szeemann, Harald -- Kunstausstellung -- Verzeichnis; Szeemann, Harald -- Catálogos; Art museum curators -- Switzerland; Art museum curators; Switzerland; Kunstausstellung -- Szeemann, Harald -- Verzeichnis; Curadores de museos de arte -- Suiza; Catalogs